Analisis Pengaruh Ukuran Perusahaan, Kualitas Audit Terhadap Audit Delay Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2019-2021 - Fiorentina Br Sebayang; Nugraeni Nugraeni (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
Thel aim ofl this researchl isl to analyzel the influence ofl audit quality andl company size on auditl delay inl manufacturing companiesl listed onl the Indonesial Stock Exchangel in 2019-2021. Purposive samplingl as a sample selection techniquel with al sample ofl 28 Propertyl and Reall Estate Sectorl manufacturing companiesl listedl on thel Indonesial Stockl Exchange inl l2019-2021. Thel results prove that audit quality and company size do notl affect auditl delay.